Implementation of Electronic Stamp Duty (E-Stamp) in Online Business Transactions: Micro, Small, and Medium Enterprises (MSMEs) in the Blok M Area - Rachma, Aqila Aulia; Rizkianti, Wardani (GoAcademica Research & Publishing, 2025)
The digitalization of online business transactions has prompted the government to introduce e-stamps as an instrument for legalizing electronic documents. However, its implementation still faces challenges, such as technical constraints, system instability, a lack of user guidelines, and low digital literacy among MSMEs and the public. This study aims to analyze the validity and effectiveness of e-stamps in online business transactions, particularly for MSMEs in the Blok M area, and to identify barriers to their implementation from a civil law and cyber law perspective. The method used is empirical juridical research with a sociological approach to law, legislation, and case studies. Primary data was obtained through interviews with MSMEs, notaries, DJP/Peruri officials, judges, and users; while secondary data came from laws and regulations and legal literature. The results show that, normatively, e-stamps are valid and have equal legal standing to physical stamps. However, their effectiveness is suboptimal due to technical constraints, limited infrastructure, and the unequal adoption of digital legal culture. Furthermore, there is no jurisprudence that specifically defines the position of e-stamps in civil cases. This study concludes that there is a need to strengthen outreach, improve infrastructure, develop uniform technical guidelines, and integrate e-stamps with digital platforms to support legal certainty and efficiency in online transactions.